(untitled) (Research, Society and Development, 2021)
In Santa Rosa de Lima - SC - Brazil, a small municipality in South Region mainly covered by Atlantic Rain Forest, there is an effort to promote agroecology as socio-ecological improvement for family farmers. Part of this effort was conducted with young farmers in a debate about their land-use practices and the consequences of diversifying their activities. This study describes the process of a participatory modeling approach carried out in a workshop with young farmers to co-design conceptual models for land use practices. As results, a system dynamics model was built to represent their reality. The results of the workshop were embedded in a model to simulate a typical local property and provide insights into the consequences of diversifying their agricultural production by using the agroecological practices. Finally, the work presents the designed model and the first outcomes of scenario simulation, discussing the use of system thinking approaches in participatory modeling.